Internalisasi Nilai Moderasi Islam dalam Membentuk Moral Santri Milenial (Studi Kasus di Pondok Pesantren Tebuireng Diwek Jombang) - Jauharoh, Nur Kholidah; Rofi’ah, Siti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) STIB Banyuwangi, 2020)
Islamic boarding schools are educational institutions that are still developing from all changes. Manifestation of the development of the pesantren which he carried had the principle of Islamic moderation in the process of developing Indonesia. As is the case with the internalization of Islamic moderation values ​​in shaping the morale of santri in the Tebuireng boarding school in Diwek Jombang, where the boarding school strongly upholds the values ​​of tolerance or tasammuh. Because we know that in the millennial era at this time, it is very important to maintain moral values ​​in aligning morals with the progress of the times, therefore the value of Islamic moderation must be maintained or applied to every human being and especially the students. Such as implementing and empowering the values ​​of moderation in Islamic boarding schools to uphold these values, due to the depletion of morals in the millennial era. The objectives of this study are: 1) to describe the value of Islamic moderation in the Tebuireng Islamic Boarding School in Jombang, 2) to describe the moral formation in the Jombang Islamic Boarding School, 3) to describe the process of internalizing Islamic values ​​in shaping the morality of the Tebuireng Islamic Boarding School in Tebuireng Islamic Boarding School in Jombang. . It is also expected to provide benefits in the development of science in the field of Islamic education and moral formation in both formal and non-formal education such as pesantren. The approach and type used is a qualitative descriptive method approach. What is meant by descriptive qualitative is looking for a picture or describing observations directly looking at phenomena and reality. Data collection techniques used were observation, interviews, and documentation. While the data analysis is data reduction, data presentation, drawing conclusions. The conclusions of the focus of the problem above: 1) the rise of extreme understanding that emerged in Indonesia in Muslims, especially among students. And encourage the students to instill and actualize moderate values ​​in the main students themselves. Therefore, the Tebuireng Islamic boarding school instills the value of Islamic moderation through the five basic values ​​of the santri: sincerity, honesty, hard work, responsibility and tasammuh / tolerance. From these five basic boarding schools apply tasammuh or tolerance which is very important in the teachings of Islam and life. 2) shaping the morality of millennial students is a must that must not be forgotten, because educating children or santri is a necessity to become a civilized and moral person, where the position that is very important at this time is a child who has manners and morals. 3) shows that the process of internalizing the values ​​of Islamic moderation in shaping the morality of millennial students in Tebuireng Islamic Boarding School, especially in Pondok Tebuireng Putra, is something that requires a very long process. In this process what is very important is himself and his environment.